(untitled) (Journal of Engineering and Health Sciences, 2019)
Statistics is one of the most important quantitative subjects in higher education. However, statistics subject is unappealing to many average students with varying background. Traditional teaching method of statistics which tend to emphasize on rote learning and heavy calculations can cause students to have negative perception thus stir anxiety towards statistics learning. Therefore, to address all these negative perceptions, it is important for educators to make a significant improvement in their teaching approach to make learning more dynamic, meaningful and inspiring. This study is aimed primarily to highlight the factors of a research instrument used to evaluate the implementation of a developed interactive learning tool namely XRace game board in providing active learning. An exploratory factor analysis suggested that out of 33 variables evaluated, there are six domains which account for 71.78% of the total variance which considerably reduce the complexity of the data set with 28.82% loss of information. Kaiser-Meyer-Olkin value is 0.895 and Bartlett’s test p-value=0.000 < 0.05 indicate factor analysis is feasible for this data set. There is no item removed since the communalities values are all above moderate (min=0.583, max=0.837). The principal component analysis with Varimax rotation method revealed six domains in term of Motivation, Novelty, Fun learning, Commercialization, Product features and Eco friendly. The results suggested that these six important domains were considered in the evaluation of the learning tool and the possibility of utilizing it in teaching any difficult courses in an interesting and engaging way without loss of rigor.